Osseous choristoma of the tongue. - Ngeow, Wei Cheong; Lian, C.B.; Shanmahasuntharam, P. (1996)
The term "choristoma" is used to describe a mass of histologically normal tissue presenting in an aberrant site. A rare case of osseous choristoma of the tongue is presented and the literature is briefly reviewed.